Pengaruh Perencanaan Anggaran dan Lingkungan Birokrasi terhadap Penyerapan Anggaran: Studi Empiris pada Satuan Kerja Perangkat Daerah di Kabupaten Tanah Datar - Syaza Furqana; Dian Fitria Handayani (Jurnal Eksplorasi Akuntansi, 2022)
The purpose of this research is to examine the effect of budget planning and bureaucratic environment on budget absorption in the government of Tanah Datar Regency. The population of this research are 24 regional work units in Tanah Datar Regency. The respondents are the head of the office, finance department, asset department and expenditure treasurer. This research used primary data that used questionnaires distributed directly to 96 respondents. The results of this research indicate that 1) budget planning has positive effect on budget absorption in regional work unit in Tanah Datar Regency 2) budget planning has positive effect on budget absorption in regional work unit in Tanah Datar Regency. The contribution of the independent variable in explaining the dependent variable in the amount of 53,5%, while the remaining 56,5% explained by other variables outside the model.